Designing a Secure and Reliable Network using EIGRP, VPN, DMZ and IDS/IPS - Soewito, Benfano; Santoso, Berkah I. (Journal of Computer and Information, 2012)
Nowadays  networking  is  not  something  new for  us,  we  have  hear  about  networking  applications  and problems  every  day  at  the  present  time.  We  can  now  easily communicate  with  each  other  despite  the  distance  apart, exchange  data,  audio,  video,  and  information. Network consists of Local Area Network (LAN) and Wide Area Network  (WAN).  Local  Area  Network  is  a  computer  network that  covers  only  a  small  area  networks,  such  as  campus computer networks, buildings, offices, homes, or schools. While the Wide Area Network is a data communications network that operates beyond the geographic scope of the LAN. Knowing the applications,  devices,  and  protocols  before  designing  the network is very important to build a reliable and safe network. We  have  designed,  build,  and  simulated  a  network  using EIGRP, VPN, DMZ and IDS/IPS. The result of our simulation shows  the  network  has  a  good  performance,  secure,  and reliable.